Secularism as a human right: learning from the European Court of Human Rights - Gülalp, Haldun (Frontiers in Sociology, 2024)
Secularism is conventionally (and somewhat misleadingly) defined as the separation of state and religion. This article offers an alternative and more refined concept of secularism as a normative political principle of social peace within the context of diversity. The argument that secularism, so understood, lies at the core of a notion of human rights, contra the critique it has been receiving in recent decades as being hostile to freedoms, is assessed conceptually and supported by an analysis of how it is (indirectly) articulated in the jurisprudence of the European Court of Human Rights.